2002
DOI: 10.4314/wsa.v28i4.4917
|View full text |Cite
|
Sign up to set email alerts
|

Metal concentrations in <i>Clarias gariepinus</i> and <i>Labeo umbratus</i> from the Olifants and Klein Olifants River, Mpumalanga, South Africa: zinc, copper, manganese, lead, chromium, nickel, aluminium and iron

Abstract: The upper catchment of the Olifants River, from its origin near Bethal to its confluence with the Wilge River, north of Witbank, and its tributaries are being subjected to increasing afforestation, mining, power generation, irrigation, domestic and industrial activities. These activities have a profound effect on the water quality. The major point sources of pollution in the study area include mines, industries and very importantly, combined sewage purification works that are located alongside the river. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
30
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 30 publications
13
30
1
1
Order By: Relevance
“…Kotze et al (1999) showed that bioaccumulation of metals in the fish studied occurred in the following order of decreasing intensity: liver>gills>skin>muscle. Further studies have confirmed these findings but in different fish such as Oreochromis niloticus, Cyprinus carpio and Labeo umbratus, Tilapia nilotica, Tilapia zilli, Clarias anguillaris, Protoptenus, Eutropius niloticus and Synodentis budgetti (Rashed, 2001;Coetzee et al, 2002;Vinodhini and Narayanan, 2008;Akan, 2009;Rauf et al, 2009). Rauf et al (2009) also obtained the same results as Kotze et al (1999) and established that the metal concentrations in the liver and gills were significantly different (p<0.01) and the minimum concentrations in the liver (4.26±1.57 and 6.23±1.14 µg/g) were higher than for gills (1.10±0.53 and 1.46±0.52 µg/g) for cadmium and chromium, respectively.…”
Section: Bioaccumulation Of Heavy Metals 261 Accumulation and Effecmentioning
confidence: 60%
See 3 more Smart Citations
“…Kotze et al (1999) showed that bioaccumulation of metals in the fish studied occurred in the following order of decreasing intensity: liver>gills>skin>muscle. Further studies have confirmed these findings but in different fish such as Oreochromis niloticus, Cyprinus carpio and Labeo umbratus, Tilapia nilotica, Tilapia zilli, Clarias anguillaris, Protoptenus, Eutropius niloticus and Synodentis budgetti (Rashed, 2001;Coetzee et al, 2002;Vinodhini and Narayanan, 2008;Akan, 2009;Rauf et al, 2009). Rauf et al (2009) also obtained the same results as Kotze et al (1999) and established that the metal concentrations in the liver and gills were significantly different (p<0.01) and the minimum concentrations in the liver (4.26±1.57 and 6.23±1.14 µg/g) were higher than for gills (1.10±0.53 and 1.46±0.52 µg/g) for cadmium and chromium, respectively.…”
Section: Bioaccumulation Of Heavy Metals 261 Accumulation and Effecmentioning
confidence: 60%
“…The gills, skeleton, kidneys, liver and muscles are the main target organs for Al toxicity in fish while the first three are the most susceptible organs to Al bioaccumulation in fish (Sharma, 2003). In contrast, Coetzee et al (2002) had shown that Al is accumulated mostly in the gill and liver tissue, followed by the muscle and skin tissues and that this uptake occurred primarily through the gills just as with any other heavy metal. These studies on Al accumulation agree that the gills are among the most susceptible to Al accumulation while the muscle accumulates the least but disagree in terms of the liver as Sharma reported that the liver and the muscle are the least susceptible.…”
Section: Bioaccumulation Of Heavy Metals 261 Accumulation and Effecmentioning
confidence: 99%
See 2 more Smart Citations
“…These mines contribute large volumes of AMD to the upper reaches of the Olifant's River catchment upstream of Lake Loskop, which acts as a repository for pollutants from the upper catchment (Oberholster et al, 2010). To the authors' knowledge, only one earlier study has been carried out on the upper Olifant's River to determine metal bioaccumulation in fish, and which included Aluminium (Al) as a toxic agent of AMD (Coetzee et al, 2002). The authors found in their study that Zn, Cu, Mn, Pb, Cr, Ni, Al and Fe preferentially accumulated in the skin, muscle, liver and gill tissues of fish with the highest metal concentrations localized to the liver and gill tissues of Clarias gariepinus and Labeo Umbratus.…”
Section: Introductionmentioning
confidence: 99%